Identificação de regiões hidrologicamente homogêneas por agrupamento fuzzy c-means no estado do Paraná - Silva, Ana Claudia Guedes (2018)
The design of hydrologically homogeneous regions (RHH) is an essential procedure to provide information essential to the modeling, planning, and management of water resources, especially when it is necessary to perform the regionalization of flows, aiming to estimate the water availability in sections without measurements. The definition of strategies for the management and conservation of natural resources depends on information obtained through the identification of RHH, also being one of the steps of a study of regionalization of flows. Thus, this work has the objective of identifying the RHH in the state of Paraná through the grouping method Fuzzy C-Means. A total of 9 variables were used for the 114 fluviometric stations, with 4 dependent variables related to the characteristic flows (annual average long-term flow (Qmld), minimum annual flow with seven days duration and 10-year return period (Q7,10), flow rates associated to the 95% (Q95) and 90% (Q90) permanencies) and 5 independent variables related to the morphometric characteristics of the station (drainage area (AD - m²), sum of drainage (SD - m) (LA - Lat and longitude - Long). From the principal components analysis (PCA), the variables Qmld, DD, Lat and Long were identified as the least representative, being discarded from the study, proceeding with the analysis using only the variables AD, SD, Q90, Q95, and Q7,10. The results were obtained using the Fuzzy C-Means for the chosen variables, and the smallest objective function was found for 4 Clusters in the study group, with index of and fuzzification (m) 1.7. Separating the fluviometric stations by clusters through degrees of pertinence, the largest number of stations were obtained in Cluster 3 (83 stations), followed by Cluster 4 (13 stations) and Clusters 1 and 2 (7 stations in each cluster), and only 4 stations were not inserted in any cluster, being classified as nebulae, where the groups were determined practically by the distribution of the AD and SD variables. The smaller areas of coverage, analyzed flows and the smaller amount of drainage in the coverage area of the stations were found in Cluster 3, considering they were well spread in the state of Paraná. Clusters 1 and 4 were intermediate among the other clusters in all parameters evaluated. The Fuzzy C-Means algorithm proved to be efficient for the grouping of fluviometric stations in the state of Paraná, where it was possible to find the characteristics of each cluster formed, without overlapping of data in the analyzed variables.